2021
DOI: 10.3389/fonc.2021.675458
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Model for Predicting a Major Response to Neoadjuvant Chemotherapy in Advanced Gastric Cancer

Abstract: AimsTo develop and validate a model for predicting major pathological response to neoadjuvant chemotherapy (NAC) in advanced gastric cancer (AGC) based on a machine learning algorithm.MethodA total of 221 patients who underwent NAC and radical gastrectomy between February 2013 and September 2020 were enrolled in this study. A total of 144 patients were assigned to the training cohort for model building, and 77 patients were assigned to the validation cohort. A major pathological response was defined as primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…5.6%-16% (16, 42, 43) and 21.2%-27.6% (44,45). In the present study, we found that the pooled pCR rate is 21.7% and that the pooled MPR rate is 44.0% in patients with LAGC who received NACT combined with immunotherapy, which seemed superior to that in patients who received NACT alone in previous studies.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…5.6%-16% (16, 42, 43) and 21.2%-27.6% (44,45). In the present study, we found that the pooled pCR rate is 21.7% and that the pooled MPR rate is 44.0% in patients with LAGC who received NACT combined with immunotherapy, which seemed superior to that in patients who received NACT alone in previous studies.…”
contrasting
confidence: 48%
“…Therefore, pCR and MPR could be used as key indicators in the selection of optimal regimens. Previous studies have demonstrated that the pCR rate and MPR rate for patients with LAGC who received NACT was mostly 5.6%–16% ( 16 , 42 , 43 ) and 21.2%–27.6% ( 44 , 45 ). In the present study, we found that the pooled pCR rate is 21.7% and that the pooled MPR rate is 44.0% in patients with LAGC who received NACT combined with immunotherapy, which seemed superior to that in patients who received NACT alone in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…By training a radiomics model, Chen et al aimed to predict response to nCRT in patients with advanced gastric cancer [ 45 ]. Out of all clinical factors, only tumor differentiation was significant for this response.…”
Section: Resultsmentioning
confidence: 99%
“…Radiomics integrates meaningful quantitative imaging features for modeling, which is a major difference from methods utilizing the traditional visual interpretation of images [35][36][37][38][39]. Chen et al [40] used the features of the CT venous phase and established a predictive model to distinguish between advanced gastric cancer patients with potentially pathologically significant reactions and those with mild reactions and were able to effectively stratify patients according to their response to NAC. Mazzei et al [41] performed a multicenter study to predict NAC response by delta radiomics in locally progressive gastric cancer.…”
Section: Discussionmentioning
confidence: 99%